1997
DOI: 10.1017/s0022215100137648
|View full text |Cite
|
Sign up to set email alerts
|

Luc's abscess - a rare complication of middle-ear infection

Abstract: A case of subperiosteal temporal abscess of otitic origin is presented. This is an unusual complication of otitis media. The pathogenesis of Luc's abscess is different from other extracranial complications of middle-ear infections in that it is notassociated with mastoid infection which results in subperiosteal pus formation. Based on our experience and the reports from the turn of the century. we present the presumptive pathogenesis and clinical features. We contend that these patients run an unexpectedly ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…This suppuration may further spread along submucousal tissue plains through the incisure of Rinvinus along the vascular elements branching from the deep aricular artery [6]. Pus then progresses between the cortical bone and periosteum leading to the development of a subperiosteal abscess [7]. This suppuration may then continue along this subperiosteal plane into the temporal region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suppuration may further spread along submucousal tissue plains through the incisure of Rinvinus along the vascular elements branching from the deep aricular artery [6]. Pus then progresses between the cortical bone and periosteum leading to the development of a subperiosteal abscess [7]. This suppuration may then continue along this subperiosteal plane into the temporal region.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed two case reports of Luc's abscess since the widespread use of antibiotic therapy [7,8]. Knappe et al described a 15-year-old female who presented with one-week history of swelling over her temple and cheek.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pre-antibiotic era, Luc's abscess often presented as a complication of otitis media and its incidence since then has dramatically reduced with widespread usage of broad spectrum antibiotics [7, 8]. In 1900, Henri Luc described it as a sub-periosteal temporal abscess of otitic origin without intraosseous suppuration and suggested the possible pathway of microorganism spread from middle ear submucosa by anatomical pathways especially via the superior meatus, incisura Rivinus and along the branches of deep auricular artery [7].…”
Section: Discussionmentioning
confidence: 99%
“…In 1900, Henri Luc described it as a sub-periosteal temporal abscess of otitic origin without intraosseous suppuration and suggested the possible pathway of microorganism spread from middle ear submucosa by anatomical pathways especially via the superior meatus, incisura Rivinus and along the branches of deep auricular artery [7]. Later this theory was supported by Le Marc’ Hadour and Chauveau in 1910 and they proposed three stages of periosteal involvement in the middle ear infection namely juxtatympanic stage, progression to entire circumference of canal skin and finally spread to sub-periosteum of temporal bone [7]. Clinically, it can be located anterior, superior or posterior to the auricle [7].…”
Section: Discussionmentioning
confidence: 99%